Objectivism the philosophy of Ayn Rand - Peikoff, Leonard (New York Penguin, 1991)
This brilliantly conceived and organized book is Dr. Leonard Peikoff?s classic text on the abstract principles and practical applications of Objectivism, based on his lecture series ?The Philosophy of Objectivism.? Ayn Rand said of these lectures: ?Until or unless I write a comprehensive treatise on my philosophy, Dr. Peikoff?s course is the only authorized presentation of the entire theoretical structure of Objectivism?that is, the only one that I know of my knowledge to be fully accurate.?
Includes bibliographical references (p. [461]-478) and index.
Keywords: Rand, Ayn--Philosophy.